Clinical characteristics and treatment management of combined large cell neuroendocrine carcinoma, a subtype of large cell neuroendocrine carcinoma - Kang, Kai; Li, Binfeng; Wang, Jianjian (Frontiers in Oncology, 2024)
Combined large cell neuroendocrine carcinoma (CLCNEC) is a rare neuroendocrine carcinoma, accounting for approximately 10% of large cell neuroendocrine carcinoma (LCNEC). Mainly composed of coexisting adenocarcinoma components, with strong invasiveness and poor prognosis. The treatment regimen for CLCNEC mainly refers to complete surgical resection as the first choice in the early stage, while patients with stage II or higher require adjuvant treatment. At present, research on CLCNEC is mostly small sample and retrospective, and there is no consensus on whether molecular typing and treatment should be carried out. There is considerable controversy over whether it should be managed as small-cell lung cancer (SCLC) or non-small-cell lung cancer (NSCLC). Therefore, in order to solve the problem of confusion in the selection of treatment regimens for CLCNEC, while also considering the therapeutic effects, this article summarizes and analyzes previous studies, fully seeks evidence, and boldly proposes new therapeutic insights: the etoposide-platinum (EP) regimen serves as the basis for adjuvant therapy; In addition, SCLC/NSCLC-CLCNEC can be distinguished based on presence of RB1 and TP53 co-mutation, and targeted therapy or NSCLC type chemotherapy including platinum + gemcitabine or taxanes (NSCLC-GEM/TAX) can be used in combination or sequentially for NSCLC-CLCNEC.